IMPLEMENTATION OF GOOD GOVERNANCE PRINCIPLES IN PUBLIC SERVICES AT DISTRICT OFFICES - Auliyah, Vinantie; Igirisa, Irawaty; Tohopi, Rustam (Administratie: Jurnal Administrasi Publik, 2025)
The purpose of this study was to determine how Responsiveness, Effectiveness and Efficiency, Justice, Accountability and Transparency are provided by public service providers at the Tolangohula District Office, Gorontalo Regency. This research method is qualitative. The results of the study indicate that the implementation of Good Governance principles in public services at the Tolangohula District Office, Gorontalo Regency has been running well but not optimally. Of the 5 sub-focuses that have been studied, namely; 1) Principle of Responsiveness, 2) Principle of Effectiveness and Efficiency, 3) Principle of Justice, 4) Principle of Accountability, 5) Principle of Transparency, there are still two sub-focuses that are not optimal, namely; 1) Principle of Effectiveness and Efficiency, this is evidenced by the fact that there are still several problems, including sub-district officials who are still less disciplined in coming to the office. So that when there are people who want to do services, they have to wait for the officials. 2) The principle of transparency, this is proven by some people who do not respond to information from the apparatus, the community feels dissatisfied with the existing notice boards for several reasons, namely the lack of clear information results in low community participation in village activities and often the information provided is incomplete or late, this shows that the implementation of transparency has not been fully optimally implemented.